Efficient routing algorithm for opportunistic networks based on network coding - Zhi REN; Zhi-hu LIU; Yu-kun YAO; Qian-bin CHEN (Tongxin xuebao)
To address the problem in opportunistic network that t existing epidemic-mechanism-based routing algorithms incur redundant communication overhead during the transmission of data packets,an efficient routing algorithm based on network coding,called NCBER (network-coding-based epidemic routing),was proposed.During the transmission of data packets,NCBER adopts an active XOR coding operation and multicast,and cancels the transmission of the Request control packets,so as to reduce the time used to transmit data packets,as well as the number of control packets.As a result,NCBER cuts down the network overhead and ortens the end-to-end delay of data packets.Theoretical analysis and extensive simulation results show that NCBER outperforms the classical epidemic routing algorithm and its improvement called MRRMR (message redundancy removal of multi-copy routing) in terms of the network overhead and the end-to-end delay,while still keeping the delivery rate at 100%.